2006
DOI: 10.1037/0022-0663.98.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Family involvement in school and low-income children's literacy: Longitudinal associations between and within families.

Abstract: Longitudinal data from kindergarten to 5th grade on both family involvement in school and children's literacy performance were examined for an ethnically diverse, low-income sample (N ϭ 281). Within families, increased school involvement predicted improved child literacy. In addition, although there was an achievement gap in average literacy performance between children of more and less educated mothers if family involvement levels were low, this gap was nonexistent if family involvement levels were high. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
202
1
25

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(244 citation statements)
references
References 46 publications
(52 reference statements)
5
202
1
25
Order By: Relevance
“…It has been shown that parental school involvement can actually compensate for disadvantages children may experience in their educational career, which are rooted in demographic differences (Dearing, Kreider, Simpkins, & Weiss, 2006). Grolnick and Slowiaczek (1994) propose three main types of involvement in their multidimensional conceptualization of parental school involvement, namely behavioral, cognitive-intellectual, and personal involvement.…”
Section: Education-related Conditions For School Adjustmentmentioning
confidence: 99%
“…It has been shown that parental school involvement can actually compensate for disadvantages children may experience in their educational career, which are rooted in demographic differences (Dearing, Kreider, Simpkins, & Weiss, 2006). Grolnick and Slowiaczek (1994) propose three main types of involvement in their multidimensional conceptualization of parental school involvement, namely behavioral, cognitive-intellectual, and personal involvement.…”
Section: Education-related Conditions For School Adjustmentmentioning
confidence: 99%
“…For instance, the linguistic development of primary school pupils depends strongly on the language environment at home (cf. Leseman and De Jong 1998;Dearing et al 2004Dearing et al , 2006Lynch 2009;Merlo et al 2007). This relates not only to differences in the parents' level of education but also to the number of different words and the complexity of sentences the children hear (cf.…”
mentioning
confidence: 99%
“…Finally, engaging families in their children's schooling is an additional strategy to support children's third-grade reading proficiency. Some research demonstrates that parents' involvement in their children's learning-including attendance at school events and home reading practices-is positively related to young children's literacy development (Dearing et al, 2006;Rodriguez and TamisLeMonda, 2011). Parent engagement programs that foster parents' abilities to support children's learning may have the potential to promote children's early reading skills (Walker, Gooze, and Torres, 2014).…”
Section: Motivating Research Literaturementioning
confidence: 99%